USE OF GEOTHERMAL ENERGY SOURCES FOR HEATING AND HOT WATER SUPPLY OF RESIDENTIAL BUILDINGS IN THE SOUTHERN REGIONS OF THE REPUBLIC OF UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2023)
The paper examines the possibilities of reducing energy consumption through the introduction of heat pumps installations for heating and cooling residential buildings in rural areas from well water in some regions of the Surkhandarya region of the Republic of Uzbekistan. Some observations of changes in the temperature of water from a well throughout the year are given . It uses the heat of well water as thermal energy.